The influence of environmental factors on growth and interactions between Embellisia allii and Fusarium oxysporum f. sp. cepae isolated from garlic - Lee, Hyang Burm; Magan, Naresh (Elsevier, 2010)
Embellisia allii results in the formation of a bulb canker and black soot on the surface of different alliums and it has been frequently detected on garlic bulbs together with the spoilage fungus, Fusarium oxysporum f. sp. cepae, which causes bulb basal plate rot. In this study, the influence of water activity (aw) and temperature on mycelial growth of E. allii and F. oxysporum f. sp. cepae, conidial size and sporulation of E. allii, interactions between E. allii and F. oxysporum f. sp. cepae, Index of Dominance (ID), and in situ virulence on garlic were examined. Mycelial growth of E. allii was optimal (5.97 mm/day) at 0.995 aw and 25 °C, slower at 30 °C. However, almost no growth occurred at 0.937 aw/30 °C. F. oxysporum f. sp. cepae grew faster than E. allii, (6.3–7.4 mm/day) at 30 °C. Interactions between E. allii and F. oxysporum f. sp. cepae were influenced by aw and temperature. Sporulation of E. allii was more abundant on PDA than on MEA, especially at high aw (0.995) and low temperature (20 °C), but almost no sporulation occurred at 30 °C regardless of nutritional medium or aw level. The spore length of E. allii was longer on PDA than MEA, and was significantly influenced by water availability. F. oxysporum f. sp. cepae was competitive against E. allii and had a higher ID value in comparison with E. allii especially at a higher temperature (30 °C). In situ virulence tests showed that E. allii was weakly virulent on the garlic bulb cloves while that of F. oxysporum f. sp. cepae was highly dependent on aw.
Keywords: Embellisia allii; Fusarium oxysporum f. sp. cepae; Water activity (aw); Temperature; Interactions